Auditoría de gestión al departamento de crédito y su relación con la toma de decisiones de la cooperativa de ahorro y crédito 13 de Abril, cantón Ventanas, período 2012 - Gaibor Cevallos, Yarely Yamali (2015)
This research was to determine the incidence of Management Audit department and its relationship with credit decisions Cooperativa de Ahorro y Crédito 13 de Abril Cantón Ventanas, period 2012. To achieve the proposed overall goal raised four specific , which consisted of analyze the organizational structure of the credit department, verify the influence of policies, assess the level of confidence that the system of internal control and check the level of fulfillment of the objectives in the department credit. Regarding the methods used to obtain information on inductive, deductive, analytical and systematic was used, while types were composed of the exploratory, descriptive and explanatory techniques were interviews and survey. According to the investigation, the following information was obtained as a result; the organizational structure of the credit department is suitable for development lending activities and is 87.50% reliable, Policies for granting credit are reliable, but presents a substantial risk level of 12.50%, so that the institution must improve these aspects. Applying COSO model I, was identified control environment credit department has a risk level of 4.75%, the risk assessment has a 30,00%, the 26,25% control activity, information communication and monitoring 16.25% to 16%, showing that the average risk is 18.65%, as occurs with the objectives, these are effectively met, demonstrating a high level of satisfaction with the achievements achieved.